Предмет: Математика,
автор: ekaterinasitnikova
Решите уравнение:
2x^2+3x-3=x^2-3x+(-2+x^2)
Ответы
Автор ответа:
0
2x^2 + 3x - 3 = x^2 - 3x - 2 + x^2
2x^2 + 3x - 3 = 2x^2 - 3x - 2
2x^2 - 2x^2 + 3x + 3x - 3 + 2 = 0
0 + 6x - 1 = 0
6x - 1 = 0
6x = 1
x = 1/6
2x^2 + 3x - 3 = 2x^2 - 3x - 2
2x^2 - 2x^2 + 3x + 3x - 3 + 2 = 0
0 + 6x - 1 = 0
6x - 1 = 0
6x = 1
x = 1/6
Похожие вопросы
Предмет: Другие предметы,
автор: eyuliya80
Предмет: Русский язык,
автор: frizey
Предмет: Биология,
автор: battalovaadelina329
Предмет: Алгебра,
автор: Аноним
Предмет: Математика,
автор: pozitiffchik